SP0112 Experiences from a national surveillance program for effects, side-effects and costs of tnf-blocking agents in sweden. (1st June 2001) - Feltelius, N
Abstract : The introduction of TNF-blockers in rheumatology has focused on the need for new systems for follow-up of new drugs. Many drugs, like the TNF-blockers have new mechanisms of actions and thus unknown side effects. The national influence on the approval of new drugs has decreased with the common European regulatory system. However the economic consequences of these often expensive treatments are to be handled on the national level. Thus for medical as well as economical reasons national efforts to collect information about recently marketed drugs are important. In a joint project the Swedish Medical Products Agency (MPA) and The Swedish Society for Rheumatology introduced a follow-up system for the new TNF-blockers when used in rheumatoid arthritis. The system was implemented already before marketing. The aim is to elaborate a system for collecting and reporting pharmacotherapy data from all rheumatology units in Sweden to assess safety and efficacy. This is to optimise treatment but also to form the basis for future surveillance programmes for other new drugs. The study started in early 1999 with a planned 2-year duration. Assessments of patients are scheduled at 0, 3, 6, 12, 18 and 24 months. Patients included are those with active RA who has failed previous DMARD treatment. All patients are treated on a named-patient-basis and are identified by a unique personal number. This system makes possible future cross-linking with other health data bases. Disease activity is measured according to EULAR core set. The concomitant use of DMARDs and other medications is recorded in detail. Treatment reports have till now been collected from 1280 patients. The overall clinical outcome of etanercept as well as of infliximab treatment is much in line with what has been reported from randomised controlled studies (RCTs). Only a small number of patients has been followed for over 12 months but efficacy seems sustained also after this time point. Reporting of adverse events (AEs) is higher in this surveillance study than what can be expected from the regular spontaneous reporting system. In total 425 AEs have been reported in the cohort. Most frequent are injection site reactions and other dermatological manifestations. Among serious adverse events infections were predominant, with cases of septic arthritis and septicaemia reported. The cost for TNF-blocker treatment in Sweden during the year 2000 is 170 million SK. The spending calculated per inhabitant indicate substancial regional differences in prescription. These figures includes treatment of Crohn's disease patients. The main conclusions from this study are: 1. Results of TNF-blocker treatment from RCTs seem valid also in an everyday clinical setting. 2. Reporting of adverse events can be substantially improved compared to the existing systems. 3. The logistics of reporting was the main problem in establishing the data collecting system. 4. The involvement of the MPA and the Swedish Society for Rheumatology was necessary to implement the system. 5. For the future the establishing of firm and independent systems that can further develop these kind of drug surveillance is highly desirable. In this struggle the participation of all key players regulatory agencies, professional societies, academic institutions and drug companies is necessary.